THE CASE FOR XENOTRANSPLANTATION - Cooper, David K. C. (Clin Transplant, 2015)
The availability of organs and cells from deceased humans for transplantation is not meeting the demand. Xenotransplantation, specifically the transplantation of organs and cells from genetically-engineered pigs, could resolve this problem. Diabetic monkeys have remained normoglycemic and insulin-independent after pig islet transplantation for >1 year, and a pig heterotopic (non-life-supporting) heart transplant recently reached the one-year milestone in a baboon. With these encouraging results, why is it that, with some notable exceptions, research into xenotransplantation has received relatively little support by industry, government funding agencies, and medical charitable foundations? Industry appears reluctant to support research that will take more than 2–3 years to come to clinical trial, and the funding agencies appear to have been “distracted” by the current appeal of stem cell technology and regenerative medicine. It has only been the willingness of living donors to provide organs that has significantly increased the number of transplants being performed worldwide. These altruistic donations are not without risk of morbidity and even mortality to the donor. Although with the best of intentions, we are therefore traversing the Hippocratic Oath of doctors to “do no harm”. This should be a stimulus to fund exploration of alternative approaches, including xenotransplantation.